Perbandingan Kadar Hemoglobin Santriwati Sesudah Konsumsi Tablet Tambah Darah Ditambah Edukasi Video Singkat Dengan Hanya Konsumsi Tablet Tambah Darah - Sari, Tiara Rinta; Surtimanah, Tuti; Ruhyat, Ejeb (Perilaku dan Promosi Kesehatan : Indonesian Journal of Health Promotion and Behavior, 2022)
Background. Anemia is a condition where the hemoglobin (Hb) level is less than 12 mg/dL. 48.9% of female adolescent in Indonesia was anemic. The main cause is iron deficiency. The efforts are promoting, preventing, and increasing consumption of iron-rich foods and giving iron tablets. Objectives. Knowing the Hb level difference of female students after consuming iron tablets accompanied by short video education with female students who only consumed iron tablets. Method. Quasi-experimental, pre-posttest with control design. The population is female students, with a sample of 37 people taken purposively. The experimental variable gave iron tablets for four weeks accompanied by a short video for the intervention group and only gave iron tablets for four weeks for the control group. The affected variable was Hb levels. Results. After the intervention, the Hb level in the intervention group increased by 0.3 mg/dL while the control group increased by 0.8 mg/dL but didn’t show a statistical difference (p>0.05). There was no statistical difference (p 0.588) in Hb level change between the intervention and control groups Conclusion. There was no statistical difference in Hb level change between the intervention and control groups.